PENGARUH SUHU, KELEMBABAN, DAN SANITASI TERHADAP KEBERADAAN BAKTERI ESCHERICIA COLI DAN SALMONELLA DI KANDANG AYAM PADA PETERNAKAN AYAM BROILER KELURAHAN KARANGGENENG KOTA SEMARANG - Achmad Ian Rudiyansyah; Nur Endah Wahyuningsih; Endang Kusumanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Poultry is one of good sources of animal protein such as eggs and meat to support the protein needs of Indonesian people. One of the efficient effortsto fulfill the needs is broiler farming business. Besides getting the expected results in the cage at the farm there are some bacteria such as Salmonella pullorum and Escherichia colithatcause diseasesin poultry which make economically lossesand are zoonotic. This study aimed to determine the effects of temperature, humidity and sanitation to the presence of bacteria Salmonella pullorum and Escherichia coli in the broiler farm. This research used True Experimental Research with research design of post-test only control group design. Samples were taken from the water jars in the treated cage and control cage. The results showed that after treated with opened lid cage within 6, 7, 8 hours and sealed cage there was only one positive sample bacterium Escherichia coli found in the 5th of repetition. Based on the data normality test using Shapiro Wilk temperature and humidity had a p-value> 0.05, it indicates that the data was normally distributed. Based on One Way Annova test for the temperature in the cage a significant value of 1,000 was obtained, which means no effect of temperature on the presence of bacteria Escherichia coli and Salmonella pullorum and for humidity the significance values was 0,990, means there was no influence of humidity on the presence of bacteria Salmonella pullorum and Escherichia coli. It can be concluded that the temperature and humidity in this study had no effect on the presence of the Escherichia coli and Salmonella pullorum bacteria on treated cage as well as in the control cage, so that the cage conditions are assumed to be healthy cage.